Analysis of Challenges and Solutions in the Management of Achmad Wardi Waqf Hospital - Rusli, M.; Mawardi, Imron; Laila, Nisful; Rusgianto, Sulistya (Journal of Posthumanism, 2025)
Background: A waqf-based eye hospital, a place where high-quality eye health services are organised with a spirit of care and sustainability. The hospital was founded on the principle of waqf, which combines elements of modern healthcare with Islamic values to provide maximum benefit to the community. Objective: This study aims to analyse the challenges and solutions for the sustainable development of waqf management implementation at Achmad Wardi Eye Hospital. Research Methodology/Design: This research will use a qualitative approach by conducting a case study of the operating Achmad Wardi waqf hospital. In-depth interviews with relevant parties, document analysis, and direct observation will be the main methods for collecting data. Results: Based on the results of the interview, there are several challenging problems that occur in each work unit of Achamd Wardi Hospital to support the main targets of the Hospital, including the target of optimising turnover and maintaining profits of Achmad Wardi Hospital, including finance, marketing, human resources and services. Managerial Implications: This research is expected to contribute to further understanding of the implementation of waqf hospitals, so that it can be a reference for related parties in establishing and managing hospitals with waqf principles.